Peptide applications in biomedicine, biotechnology and bioengineering - Koutsopoulos, Sotirios (Woodhead Publishing series in biomaterials, 2018)
Peptide Applications in Biomedicine, Biotechnology and Bioengineering summarizes the current knowledge on peptide applications in biomedicine, biotechnology and bioengineering. After a general introduction to peptides, the book addresses the many applications of peptides in biomedicine and medical technology. Next, the text focuses on peptide applications in biotechnology and bioengineering and reviews of peptide applications in nanotechnology. This book is a valuable resource for biomaterial scientists, polymer scientists, bioengineers, mechanical engineers, synthetic chemists, medical doctors and biologists.--Provided by publisher.